Transgenic expression of HuR increases vasogenic edema and impedes functional recovery in rodent ischemic stroke. (20th November 2017) - Ardelt, Agnieszka A.; Carpenter, Randall S.; Iwuchukwu, Ifeanyi; Zhang, An; Lin, William; Kosciuczuk, Ewa; Hinkson, Cyrus; Rebeiz, Tania; Reitz, Sydney; King, Peter H.
Highlights: Transgenic expression of HuR in astrocytes worsens short-term stroke outcome. Brains of transgenic mice with stroke exhibit more edema compared to littermates. Cerebral vascular permeability is increased in transgenic mice with stroke. Abstract: Background and purpose: Ischemic stroke produces significant morbidity and mortality, and acute interventions are limited by short therapeutic windows. Novel approaches to neuroprotection and neurorepair are necessary. HuR is an RNA-binding protein (RBP) which modulates RNA stability and translational efficiency of genes linked to ischemic stroke injury. Methods: Using a transgenic (Tg) mouse model, we examined the impact of ectopic HuR expression in astrocytes on acute injury evolution after transient middle cerebral artery occlusion (tMCAO). Results: HuR transgene expression was detected in astrocytes in perilesional regions and contralaterally. HuR Tg mice did not improve neurologically 72 h after injury, whereas littermate controls did. In Tg mice, increased cerebral vascular permeability and edema were observed. Infarct volume was not affected by the presence of the transgene. Conclusions: Ectopic expression of HuR in astrocytes worsens outcome after transient ischemic stroke in mice in part by increasing vasogenic cerebral edema. These findings suggest that HuR could be a therapeutic target in cerebral ischemia/reperfusion.